Chemical Properties and Total Plate Count of Dodol Packaged in Active Packing with the Addition of Klutuk Banana Leaf (Musa balbsiana Colla) Extract - Rahmadhia, Safinta Nurindra; Sigit, Naufal Haudry; Juwitaningtyas, Titisari (Journal Akademik Universitas Swiss German, 2024)
Active packaging is packaging designed to extend shelf-life or to maintain or improve the quality of packaged food. The concept of active packaging is to add certain components to the packaged food system or the surrounding environment. Dodol is a perishable food because it has a high-water content. The deterioration typically manifests as the presence of microbial growth and rancidity on the dodol. To increase the shelf life and quality of dodol is by wrapping it with active packaging. This study aimed to determine the effect of using active packaging on the chemical properties (water content, peroxide number, and antioxidant activity) and total plate count (TPC) of dodol. Active packaging made from cassava starch with the addition of klutuk banana leaf extract (KBLE) of the wulung variety as a source of antioxidant compounds is made by casting method. This research was conducted in two variables, namely the Wulung variation of KBLE concentration (0% and 20% w/v) and storage time (0; 5; 10; 15; 20; 25; and 30 days). The results of this study indicate that the active packaging (F2) applied to dodol has a significant effect (p<0.05) on the water content, peroxide value, antioxidant activity, and TPC values of dodol. Dodol packaged using active packaging after 30 days had lower water content, peroxide value, and TPC values than dodol packaged without KBLE. In addition, the value of antioxidant activity in dodol and active KBLE packaging obtained higher values (37.5% on days 30th) than packaging that was not given KBLE.